The psychology of animal companionship: Some ancient and modern views - Viviers, Hennie (HTS teologiese studies, 2014)
The intuitive sensing of a mental bond between ourselves and animals, especially those that live very close to us, our companion animals, has been there since early history. Some ancient Israelite views testify to an irresistible anthropomorphising of their domestic animals (Jn 3:5–9) as well as an acknowledgement of the socio-psychological support provided by them (2 Sm 12:1c–4d). Is there indeed a mental overlap between humans and animals to explain this intuitive experiencing of a bond between ourselves and them since ancient times? Modern neuroscience, through neuro-imaging, has shown that dogs (at least) are able to reciprocate our thoughts and feelings, be it in a limited way. They seem to have some limited form of a ‘theory of mind’ previously ascribed to humans only. This explains why they have been humans’ ‘best friend’ for the past 12 000 years since they were domesticated from wolves. The intuitions of the ancients and the findings of modern science confirm that we and non-human animals all form intrinsically part of the fascinating web of life. This fact should sensitise us as moral agents to preserve this life.